The Forgotten Islands: Monitoring Tourist Numbers and Managing Tourism Impacts on New Zealand’s Subantarctic Islands - Stewart E; Espiner S; Liggett D; Taylor Z (Resources, 2017)
Situated to the south of New Zealand in the Southern Ocean are the New Zealand Subantarctic Islands, comprising the Auckland, Campbell, Antipodes, Snares and Bounty Islands. Sometimes referred to as the ‘Forgotten Islands’, these island groups are among the most remote and hostile within New Zealand waters. Yet, as they harbour some of the country’s most unique biodiversity and contain some of the world’s least modified landforms, they were recognized in 1998 with the designation of World Heritage Area status. It is not surprising therefore that the Islands have long appealed to visitors wishing to explore and understand the Islands’ rich natural and cultural environments. Typically, fare-paying tourists arrive by sea in small- to medium-sized expedition-style cruise vessels, although in recent years, the number of small vessels, such as yachts and sail boats, has increased. The most recent Conservation Management Strategy (2016) proposes developing and implementing a visitor monitoring programme to determine the effects of visitors on the natural and cultural environment, as well as on the visitor experience itself. However, there is only piecemeal data published on visitor numbers (especially since the mid-1990s) upon which to base visitor monitoring, and there is only limited evidence regarding the range of possible impacts visitors may have, including direct and indirect impact on wildlife, soils, and vegetation. In order to address this gap in knowledge, this case study draws on stakeholder interviews (n = 4), and a range of secondary sources (including visitor statistics from the Department of Conservation, tour operators and other published works) to provide an overview and update on visitation to the Islands, including site-specific data, an assessment of tourist impacts, and how impacts are currently monitored and managed.